The Development Training Model for the Production of Local Material-Based Artificial Fish Feed in Jelimpo District Landak Regency - Anita, Yopi; Sudana, I Made; Wibawanto, Hari (Universitas Negeri Semarang, 2019)
Feed is one of important components in fish farming, around 60% of the operational cost is spent on feeds. The government initiated Gerakan Pakan Mandiri (GERPARI) or independent feed movement to minimalize the dependency on commercial feed also to minimalize the dependency on imported feed material by utilizing the abundant local materials. However, the potential of local raw materials abundance has not been able to be optimally managed due to the lack of knowledge of farmers, consequently, farmers have not been able to escape the dependency on commercial feed. The development of this training model is a medium which is expected to be able to improve the economy of the underdeveloped rural communities by increasing the value of agricultural products. The purpose of this study is 1) to identify and evaluate the training model carried out using training materials and personal training models, 2) develop the training model that are expected to optimize the improvement of knowledge and skills, 3) analyze the effectiveness of the training model. The approach used in this study refers to research and development (R & D) research. The development research procedure adopted the modified steps from Sugiyono, including: (1) the potential and problems; (2) data collection; (3) training model design; (4) validation of the training model; (5) revision of the training model; (6) limited trials of training models; (7) the final model. The results of the research on the development of training models for making artificial fish feed have been validated by experts using the Aiken's V formula with a validity coefficient of> 0.30, the results of the pretest and posttest of all participants increased consequently the developed model can be applied. Feeds resulted from the training are usable since it was responded by the fish. Unfortunately it is not waterproof. The training program is considered practical because it received positive responses from the participants. This research produced a valid, effective and practical feed production training model.